Quantum well laser: modelling of optical transition in quantum well with various barrier heights / Siti Salwa Misran - Misran, Siti Salwa (2007)
A quantum well is a potential well that refers to discrete units assign to certain physical quantities. This "well" is like a box in which particles can be trapped, in much the same way that light can be trapped between mirrors. These trapped particles is in quantum confinement. The quantum confinement effects restrict what the carriers can do. In a quantum well, they can move freely sideways in the plane of the layer but are confined in the forwards-backward direction. For any particular sideways speed, there could now be several different ways in which the carrier is confined in the layer. These quantum wells have many useful properties because we can engineer the forward-backward confinement exactly and they are relatively easy to make. An understanding of the physical properties of heterostructures is essential to their successful use in devices. As a result, they are now widely used to make semiconductor lasers and other useful devices. The heterostructures provide a wealth of physical phenomena and design options that may be exploited in advanced semiconductor devices.